Deep learning with MXNet cookbook discover an extensive collection of recipes for creating and implementing AI models on MXNet - Torres, Andrés P. (Packt Publishing, 2023)
Gain practical, recipe-based insights into the world of deep learning using Apache MXNet for flexible and efficient research prototyping, training, and deployment to production Key Features Create scalable deep learning applications using MXNet products with step-by-step tutorials Implement tasks such as transfer learning, transformers, and more with the required speed and scalability Analyze model performance and fine-tune for accuracy, scalability, and speed Purchase of the print or Kindle book includes a free PDF eBook Book Description Explore the capabilities of the open-source deep learning framework MXNet to train and deploy neural network models and implement state-of-the-art (SOTA) architectures in Computer Vision, natural language processing, and more. The Deep Learning with MXNet Cookbook is your gateway to constructing fast and scalable deep learning solutions using Apache MXNet. Starting with the different versions of MXNet, this book helps you choose the optimal version for your use and install your library. You'll work with MXNet/Gluon libraries to solve classification and regression problems and gain insights into their inner workings. Venturing further, you'll use MXNet to analyze toy datasets in the areas of numerical regression, data classification, picture classification, and text classification. From building and training deep-learning neural network architectures from scratch to delving into advanced concepts such as transfer learning, this book covers it all. You'll master the construction and deployment of neural network architectures, including CNN, RNN, LSTMs, and Transformers, and integrate these models into your applications. By the end of this deep learning book, you'll wield the MXNet and Gluon libraries to expertly create and train deep learning networks using GPUs and deploy them in different environments. What you will learn Grasp the advantages of MXNet and Gluon libraries Build and train network models from scratch using MXNet Apply transfer learning for more complex, fine-tuned network architectures Address modern Computer Vision and NLP problems using neural network techniques Train state-of-the-art models with GPUs and leverage modern optimization techniques Improve inference run-times and deploy models in production Who this book is for This book is for data scientists, machine learning engineers, and developers who want to work with Apache MXNet for building fast and scalable deep learning solutions. Python programming knowledge and access to a working coding environment with Python 3.6+ is necessary to get started. Although not a prerequisite, a solid theoretical understanding of mathematics for deep learning will be beneficial.
Keywords: Apache MXNet; Machine learning; Apprentissage automatique